A new physical simulation tool to predict the interface of dissimilar aluminum to steel welds performed by friction melt bonding. Issue 9 (September 2019) - Sapanathan, T.; Jimenez-Mena, N.; Sabirov, I.; Monclús, M.A.; Molina-Aldareguía, J.M.; Xia, P.; Zhao, L.; Simar, A.
Abstract: Optimization of the intermetallic layer thickness and the suppression of interfacial defects are key elements to improve the load bearing capacity of dissimilar joints. However, till date we do not have a systematic tool to investigate the dissimilar joints and the intermetallic properties produced by a welding condition. Friction Melt Bonding (FMB) is a recently developed technique for joining dissimilar metals that also does not exempt to these challenges. The FMB of DP980 and Al6061-T6 was investigated using a new physical simulation tool, based on Gleeble thermo-mechanical simulator, to understand the effect of individual parameter on the intermetallic formation. The proposed method demonstrates its capability in reproducing the intermetallic characteristics, including the thickness of intermetallic bonding layer, the morphology and texture of its constituents (Fe2 Al5 and Fe4 Al13 ), as well as their nanohardness and reduced modulus. The advantages of physical simulation tool can enable novel developing routes for the development of dissimilar metal joining processes and facilitate to reach the requiring load bearing capacity of the joints.